Hemolytic Anemia and Thrombocytopenia with Hyperthyroidism : A Case Report - Jha, NM; Adhikari, B; Thapa, A; Mishra, A; Maskey, R (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Hemolytic anemia occurs when there are low number of red blood cells due to excess of hemolysis in the body. Thrombocytopenia is a condition that occurs when the platelet count is too low. Hyperthyroidism is when the thyroid gland makes more thyroid hormones than the body needs. Only a few cases of hyperthyroidism associated with hemolytic anemia and thrombocytopenia have been reported. We report a case of a 50 year old female, a case of Type 2 diabetes mellitus who presented with symptoms of hyperthyroidism, anemia and thrombocytopenia. Blood investigations were done which showed findings suggestive of primary hyperthyroidism and hemolytic anemia. She was managed with blood transfusion, insulin and steroid. This case highlights, though rare, hemolytic anemia and thrombocytopenia in a setting of hyperthyroidism.